Cerebrovascular compromise and cognitive decline driven by chronic heart failure - Zhao, Chenjia; Du, Fengjun; Hou, Xiaoxia; Wu, Guanhui; Cheng, Xiaoyu; Cheng, Qingzhang; Feng, Hongxuan; Zhu, Hao; Wang, Meixia (Frontiers in Neurology, 2025)
ObjectiveThis study investigated the effects of chronic heart failure with decreased LVEF on small cerebral vascular disease (CSVD) and associated cognitive impairment.MethodsThis study encompassed a cohort of 73 patients diagnosed with chronic heart failure (CHF) at the Cardiovascular Department of Suzhou Municipal Hospital, spanning the period from June 2018 to August 2022. Participants were stratified into two groups based on a left ventricular ejection fraction (LVEF) threshold of 50%: 40 patients were categorized into the LVEF≥50% group, representing 54.8% of the cohort, while 33 patients were assigned to the LVEF<50% group, constituting 45.2% of the cohort. Each subject underwent a series of assessments, including brain magnetic resonance imaging (MRI), cardiac ultrasound, and neurocognitive function tests. For the analysis of diffusion tensor imaging (DTI), the tract-based spatial statistics (TBSS) method was employed to evaluate the DTI parameters of the participants’ brain white matter. Due to the extended duration of the DTI examination and the stringent requirements for patient compliance, only 37 patients, accounting for 50.7% of the total cohort, completed the DTI scans. This subset included 20 patients from the LVEF≥50% group and 17 patients from the LVEF<50% group.ResultsIn patients with congestive heart failure (CHF) and a left ventricular ejection fraction (LVEF) of less than 50%, the total Montreal Cognitive Assessment (MoCA) score was significantly lower compared to those with an LVEF of 50% or greater (p < 0.001). Among the four common types of cerebral small vessel disease (CSVD), the occurrence of white matter hyperintensities (WMH) (odds ratio = 0.228, 95% confidence interval [0.055, 0.949], p = 0.042) was found to be associated with LVEF in CHF patients, independent of the severity of WMH. Furthermore, LVEF in CHF patients demonstrated a positive correlation with total MoCA scores, as well as with visuospatial/executive functions, attention, and delayed recall. Tract-based spatial statistics (TBSS) analysis revealed that, in comparison to CHF patients with LVEF ≥ 50%, those with LVEF < 50% exhibited a significant decrease in fractional anisotropy (FA) and significant increases in mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD). In CHF patients, FA was positively correlated with visuospatial/executive functions, attention, and delayed recall, whereas MD, AD, and RD were negatively correlated with these cognitive domains.ConclusionChronic heart failure is significantly associated with the presence of CSVD (especially WMH) and the severity of cognitive impairment, with decreased LVEF correlating with worse outcomes.